Amide-halamine/silica composite nanofibrous membranes with rechargeable chlorination function for mercaptan degradation. (June 2021) - Dai, Jianwu; Yan, Zishuo; Jiao, Wenling; Yin, Xia; Si, Yang; Yu, Jianyong; Ding, Bin
Abstract: It is an urgent need to develop an effective and advanced technique to degrade mercaptan, a kind of pollution gas with bad odor, which seriously endangers human health and living environment. However, this is still a huge challenge. Here, we have prepared amide-halamine/silica composite nanofibrous membranes possessing rechargeable chlorination capacity via the combination of electrospinning and grafting reaction. The resultant chlorinated composite membranes are endowed with great structural stability attributed to covalent binding between amide-halamine compound and silica nanofibers, and exhibit the intriguing properties of renewable chlorination performance, high active chlorine content and good water swelling resistance, which are highly capable for degrading mercaptan in sewage with high degradation efficiency and large processing flux. More importantly, the successful fabrication of the amide-halamine/silica composite nanofibrous membranes with excellent properties will open a new approach for the design and development of a potential mercaptan degrading materials in wastewater treatment. Highlights: The intrinsically rechargeable amide-halamine moieties are covalently incorporated into silica nanofibers. The composite membranes exhibited satisfactory flexibility, acid resistance and water swelling resistance. The composite membranes exhibited a robust degradation performance of mercaptan.